The Effect Of Liquidity And Business Volume On Cooperative Performance - Tutik Arniati; muslichah muslichah; Nunung Nurastuti Utami (Yayasan Hisnul Muslim Lombok, 2024)
In contemporary financial discourse, the concepts of liquidity, business volume and financial performance occupy a central position in the cooperative savings and loan business. Analysis of the impact of liquidity and business volume on cooperative performance is the objective of this study. The research population consisted of 88 cooperative savings and loan institutions located in Malang City. A purposive sampling technique was employed to choose the sample, resulting in the acquisition of 61 samples. The study findings suggest that there is no impact of liquidity on cooperative business performance. In contrast, the level of business activity impacts the performance of cooperatives. This finding provides practical implications for cooperatives that resources typically used to maintain liquidity could be better utilized in growth initiatives, such as expanding membership or diversifying services.